HOLISTIC APPROACH UPON ORIGIN AND CURE OF DISEASES IN SUSHRUT SAMHITA - Arora, Nishi; Kumar, Praveen (International Journal of Research -GRANTHAALAYAH, 2018)
The definition of disease provided in the ancient Indian text Sushrut Samhita is found to be quite similar to the one provided in the contemporary times, both meaning dis-ease. Disease has been explained clearly and succinctly in this ancient text written by Aacharya Sushrut. Aacharya Sushrut is known as ‘God of Surgery’, not only in India but all throughout the world. Sushrut Samhita was chosen to illustrate the principle of Hoslistic approach to the origins and cures of diseases. The method selected was, explaining the relevant original verses in light of their most popular commentary ‘Nirantarpad Vyakhya’ by Aacharya Danhan. Aacharya Sushrut has defined ‘disease’ in the most simplified manner along with expressing a holistic approach to the origins and cures of these diseases. In this paper, this kind of holistic approach will be discussed in detail. Though the subject of origin of diseases and their cures is very wide, Aacharaya Sushrut has compiled the answers of such questions in a very concise and comprehensive manner.